The owl service - Garner, Alan, 1934- (London : HarperCollins Children's Books, 2017)
Winner of both the Guardian Award and the Carnegie Medal, this is an all-time classic, combining mystery, adventure, history and a complex set of human relationships. Featuring a new introduction by Philip Pullman. Read less
ISBN in book previously used for other editions.
Originally published: London : William Collins Sons and Company Ltd, 1967.
Keywords: Space and time -- Juvenile fiction; Space and time -- Fiction; Wales -- Juvenile fiction; Wales -- Fiction